STRATEGI PENGEMBANGAN SARANA DAN PRASARANA PEMBELAJARAN DI PONDOK PESANTREN RASYIDIYAH KHALIDIYAH (RAKHA) AMUNTAI - Raihan Fikri; Syahrani (CV. ADIBA AISHA AMIRA, 2023)
Various kinds of important processes in education, one of which is facilities and infrastructure. If in a scope of education the facilities and infrastructure are managed properly then of course it is very influential for students because these facilities and infrastructure are very important in supporting a learning process. To get these quality facilities and infrastructure, a strategy is needed in their management and there must also be supporting factors such as human resources who are trained and appropriate in their fields. If there is a strategy in the management of facilities and infrastructure, it is hoped that the learning process runs smoothly and needs are met.